2012
DOI: 10.1371/journal.pgen.1002772
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ATRX, Genome Instability, and an Altered DNA Damage Response Are Hallmarks of the Alternative Lengthening of Telomeres Pathway

Abstract: The Alternative Lengthening of Telomeres (ALT) pathway is a telomerase-independent pathway for telomere maintenance that is active in a significant subset of human cancers and in vitro immortalized cell lines. ALT is thought to involve templated extension of telomeres through homologous recombination, but the genetic or epigenetic changes that unleash ALT are not known. Recently, mutations in the ATRX/DAXX chromatin remodeling complex and histone H3.3 were found to correlate with features of ALT in pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

43
553
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(621 citation statements)
references
References 57 publications
(60 reference statements)
43
553
1
4
Order By: Relevance
“…When we looked for colocalization of ATRX with telomeres, we did not find any significant differences between in ATRX colocalization with telomeres in the mESC E14 and 408 cell lines ( Supporting Information Figs. S3A and 3B), whereas the two mESC lines showed high frequencies of ATRX in contrast to published work where ATRX was mutated in the ALT‐positive human cells, including U2OS (Lovejoy et al, 2012). Finally, when we looked at colocalization of BRCA1 with ATRX and BLM (Figs.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…When we looked for colocalization of ATRX with telomeres, we did not find any significant differences between in ATRX colocalization with telomeres in the mESC E14 and 408 cell lines ( Supporting Information Figs. S3A and 3B), whereas the two mESC lines showed high frequencies of ATRX in contrast to published work where ATRX was mutated in the ALT‐positive human cells, including U2OS (Lovejoy et al, 2012). Finally, when we looked at colocalization of BRCA1 with ATRX and BLM (Figs.…”
Section: Resultscontrasting
confidence: 71%
“…A recent study indicated that mutations in ATRX (alpha thalassemia/mental retardation syndrome X‐linked) are associated with ALT activation in 90% of human ALT‐positive cells (Lovejoy et al, 2012). As expected, the U2OS cell line did not show staining with the ATRX antibody in contrast to nonALT cell lines ( Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Though its functional significance remains to be tested, the reduction in chromatin-bound CENP-A raises a possibility that centromere instability in cancer cells may be in part due to compromised functionality of CENP-A and CCAN proteins. In U2OS cells, ATRX is deleted and telomere is maintained via the alternative lengthening of telomeres (ALT) pathway (30). It has been recently shown that C-SCE is enhanced in mouse embryos lacking ATRX, and suggested that this hyperrecombination may result in chromosome breakage at the centromere and fusion (25).…”
Section: Cenp-a-dependent Mechanism To Maintain Centromere Integritymentioning
confidence: 99%
“…Subsequent studies have reported frequent ATRX loss (but not DAXX loss) in astrocytoma, leiomyosarcoma, dedifferentiated liposarcoma and other tumor types, and the loss of ATRX has been highly correlated with the alternative lengthening of telomeres phenotype. 6,12,13,[17][18][19][20][21] However, knockdown of ATRX or DAXX has not led to alternative lengthening of telomeres, and patients with germline ATRX mutations do not appear to be cancer prone. 18,22 In addition, although loss of either ATRX or DAXX is perfectly associated with alternative lengthening of telomeres in pancreatic neuroendocrine tumors, the situation is more complex in sarcomas.…”
mentioning
confidence: 99%
“…6,12,13,[17][18][19][20][21] However, knockdown of ATRX or DAXX has not led to alternative lengthening of telomeres, and patients with germline ATRX mutations do not appear to be cancer prone. 18,22 In addition, although loss of either ATRX or DAXX is perfectly associated with alternative lengthening of telomeres in pancreatic neuroendocrine tumors, the situation is more complex in sarcomas. In our previous studies, only approximately half of alternative lengthening of telomerespositive leiomyosarcomas and pleomorphic liposarcomas were ATRX deficient, 6,12 but alternative lengthening of telomeres was highly correlated with loss of ATRX in angiosarcomas and dedifferentiated liposarcomas.…”
mentioning
confidence: 99%